Evaluasi Sistem Proteksi Kebakaran Aktif dan Sarana Penyelamatan Jiwa Rumah Sakit Sebagai Upaya Mitigasi Kebakaran dan Kecelakaan Kerja - Wulandari, Puri; Tama, Anjab Putra (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2025)
Hospitals are workplaces with a high risk of severe consequences in the event of fire. This study aimed to evaluate the active fire protection system and life safety facilities at Hospital X Jakarta. The research employed a descriptive qualitative design using methodological triangulation through in-depth interviews with eight informants, direct observations, and document reviews. Data were analyzed by reduction, presentation, and conclusion drawing. Findings were compared with the Regulation of the Minister of Public Works No. 26/PRT/M/2008 and the standards of the National Fire Protection Association (NFPA). Of the two utility components analyzed, active fire protection systems and life safety facilities, with a total of 80 indicators, 93.44% complied with the standards, with a reliability rate of 92.5% (active fire protection systems 55% and life safety facilities 37.5%). However, several indicators remain suboptimal, particularly in equipment maintenance and evacuation route readiness. Hospitals should strengthen the maintenance of life safety facilities and conduct regular training to ensure optimal readiness of fire protection systems.